2001
DOI: 10.1152/ajpheart.2001.280.3.h1368
|View full text |Cite
|
Sign up to set email alerts
|

Coupling interval from slow to tachycardiac pacing decides sustained alternans pattern

Abstract: We discovered that the coupling beat interval from a slow to a tachycardiac pacing period considerably affected the pattern of the beat-to-beat alternation of the tachycardia-induced sustained contractile alternans. We analyzed the relationship between the coupling interval and the pattern and amplitude of the alternans in the isovolumic left ventricle of canine blood-perfused hearts. The alternans pattern and amplitude varied transiently over the first 30-50 beats and became gradually stable over the first mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The present pacing rates were much lower than the pacing rates (250-300 beats/min) that caused sustained alternans in excised, cross-circulated canine hearts [22]. Besides, we have already found that the PES contractility alternans decay consistently exists within the heart rate range of 100-150 beats/min produced by para-Hisian pacing after atrioventricular block in the excised, cross-circulated normal canine hearts under physiological conditions [9].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The present pacing rates were much lower than the pacing rates (250-300 beats/min) that caused sustained alternans in excised, cross-circulated canine hearts [22]. Besides, we have already found that the PES contractility alternans decay consistently exists within the heart rate range of 100-150 beats/min produced by para-Hisian pacing after atrioventricular block in the excised, cross-circulated normal canine hearts under physiological conditions [9].…”
Section: Discussionmentioning
confidence: 50%
“…The pacing rate was set at 163Ϯ36 beats/min (range: 90-200 beats/min) slightly above the spontaneous sinus rates in the respective hearts. These pacing rates were higher on average than the sinus rates (60-120 beats/min) in conscious dogs, but still much lower than 250-300 beats/min that could cause sustained alternans in the normal excised, cross-circulated canine hearts [22]. The anesthesia per se did not suppress canine cardiac conditions to the extent that the sustained PES alternans could occur even at the present pacing rate [7,23].…”
Section: Introductionmentioning
confidence: 58%
“…7. Apart from the triggered ischemic alternans men-tioned above, the only other two instances of ͕1:1↔2:2͖ bistability of which we are aware occur in the mechanical contraction of the heart [78][79][80] and in periodic driving of modified forms of the space-clamped Beeler-Reuter equations. [22][23][24] In the latter case, the behavior is different from ours, in that the 2:2 cycle is made up of two full-sized action potentials ͓compare, e.g., the inset in Fig.…”
Section: Triggered Alternansmentioning
confidence: 85%
“…5,6,8 There is also evidence for this bistability ͑indeed, perhaps multistability or neutral stability͒ during mechanical alternans of the nonischemic ventricle. [78][79][80] Thus, by our definition of triggered alternans, it is important to rule out the possibility that there is a pre-existing very-low-amplitude alternans present ͓see, e.g., Fig. 3 of Ref.…”
Section: Triggered Alternansmentioning
confidence: 99%
See 1 more Smart Citation